A Mail Discrimination Study using Network Basis Tools - Ozdemir, M.; Kilic, E. (Institute of Electrical and Electronics Engineers Inc., 2016)
Today, many methods used for the junk e-mail (spam) discrimination. For example, blacklists and some machine learning methods. Blacklists consists of IP addresses and domain names of spammers who previously sent e-mails and caught as spam. Machine learning methods are also among many other studies in which many studies have been done in recent years. Trained machines using e-mail header information, e-mail content and sender domain information decide newly incoming e-mail messages as spam or not. In this study, a new spam filtering technique which uses machine learning with Support Vector Machine (SVM) using header information of an e-mail and some networking tools have been proposed. © 2016 IEEE.
Ağ Tabanlı Araçlar Kullanılarak Bir E-Posta Ayırtırma Çalışması
Keywords: DNS; Reverse DNS; Spam Discrimination; SPF Record; Support Vector Machines